Kakak tumbuh kembang (KUMBANG): Engaging medical students for screening and detecting growth and developmental delays in children - Zulfikar Ihyauddin; Reza Pandu Aji; Dwi Astuti Dharma Putri; Jeslyn Tengkawan; Ayu Anandhika Septisari (Journal of Community Empowerment for Health, 2022)
ABSTRACT The current COVID-19 situation has disrupted routine growth and developmental screening programs for children delivered by the Community Health Centers (Puskesmas). The KUMBANG project aims to provide a ‘new normal’ alternative in screening for children's growth and development by involving medical students and using online platforms. This study aimed to assess the project’s reach in screening growth and developmental delays while also exploring the project’s effectiveness through parents' perspectives.Collaborating with the Center for Indonesian Medical Students’ Activities (CIMSA) Universitas Gadjah Mada, we recruited and trained 33 volunteers. Volunteers screen for children’s development through an online platform, while the community volunteer cadres measure children’s growth through COVID-safe offline appointments. We analyzed children's growth using the WHO Anthro Survey Analyzer and children's development according to the Kuesioner Pra Skrining Perkembangan guidelines. Parents' perspective on this project was assessed through a survey.A total of 92 under-five years old children from four Posyandu in Puskesmas Gondokusuman participated in the project. Around 29% (27/92) of the children had nutritional problems, either underweight, stunted, wasted, or a combination. Meanwhile, 34% (29/84) of children were at risk of developmental delays, of which five were suspected to have developmental delays, while 24 had dubious results. Parents reported that this method is sufficiently effective in screening for children's development and were comfortable with the online screening, since it is more COVID-safe. Parents also felt comfortable communicating with volunteers and believed that the medical students could provide valid and reliable information.KUMBANG project offers a good alternative for screening children's growth and development during the current disrupted routine screening. Involving medical students could help in service delivery, since health professionals are relatively occupied with COVID-19 management. The online method used in this project should be considered as a prospective option for routine screening.